2012
DOI: 10.5301/jn.5000093
|View full text |Cite
|
Sign up to set email alerts
|

Pitfall in nephrology: contrast nephropathy has to be differentiated from renal damage due to atheroembolic disease

Abstract: In a setting regarding millions of patients and millions of dollars/year, in order to clarify the true renal damage directly related to CM, we ask for prospective studies differentiating cohorts receiving intravenous and intra-arterial, transradial and transfemoral injections, and clinically relevant renal outcomes, thus avoiding the dangers that can come from the idolatry of a surrogate end point such an asymptomatic 25% transient increase of serum creatinine. To avoid that, patients may lose the possibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 56 publications
0
17
0
2
Order By: Relevance
“…However, this evidence is based on studies with intra-arterial contrast administration. More recent studies have demonstrated that the risk of CIN is minimal when the eGFR (glomerular filtration rate) is above 45 ml/min/1.73 m 2 [26,27,28,29]. Preventive measures such as pre-hydration can decrease the risk of CIN.…”
Section: Resultsmentioning
confidence: 99%
“…However, this evidence is based on studies with intra-arterial contrast administration. More recent studies have demonstrated that the risk of CIN is minimal when the eGFR (glomerular filtration rate) is above 45 ml/min/1.73 m 2 [26,27,28,29]. Preventive measures such as pre-hydration can decrease the risk of CIN.…”
Section: Resultsmentioning
confidence: 99%
“…Although the existence of CIN appears to be supported by some animal model data and a myriad of medical literature, the causal association between the administration of IV iodinated contrast medium and CIN remains controversial for several reasons (11)(12)(13)(14)(15)(16). First, it has been proposed that the "multiple-insult animal model" has poor applicability to human renal disease because of the use of multiple exaggerated nephrotoxic insults (17,18).…”
Section: Data Sources and Searchesmentioning
confidence: 96%
“…Intraarterial administration of contrast medium, performed predominantly for angiocardiographic procedures, has been reported to be associated with a higher incidence of AKI, dialysis, and mortality, as compared with IV contrast medium administration (11,53). It is uncertain whether these higher incidences are attributable to the route of administration, differences in AKI susceptibility among patients who undergo procedures with intraarterial versus IV administration of contrast medium or to iatrogenic causes from the procedures themselves (13,16). Controlled studies comparing intraarterial contrast medium-exposed and contrast medium-unexposed patients are not possible, as contrast medium administration is inherent to these procedures, with the rare exception of CO 2 angiography.…”
Section: Evidence-based Practice: Acute Kidney Injury After Contrast mentioning
confidence: 96%
See 1 more Smart Citation
“…Such as alteration in renal hemodynamic, rheological properties, endocrine and paracrine factors (adenosine, endothelin and reactive oxygen species), hyper-osmolar and hyperviscious alteration of intratubular fluids and direct cytotoxic effects on renal tubular cell. 18 Although, the eGFR is associated with higher risk of acute kidney injury as denned by Creatinine, this risk is independent or exposure to contrast material. 19 Iso-osmoler and Low-osmolar contrast media are less likely than other types of contrast to be associated with CIN.…”
Section: Discussionmentioning
confidence: 99%